2016
DOI: 10.3390/geosciences6030041
|View full text |Cite
|
Sign up to set email alerts
|

Turtles From an Arkadelphia Formation—Midway Group Lag Deposit (Maastrichtian—Paleocene), Hot Spring County, Arkansas, USA

Abstract: The Arkadelphia Formation-Midway Group (Maastrichtian-Paleocene) contact near Malvern, Arkansas preserves a K-Pg boundary assemblage of turtle species consisting of skull, shell, and non-shell postcranial skeletal elements. The Malvern turtles are preserved within a coquina lag deposit that comprises the basalmost Midway Group and also contains an abundance of other reptiles, as well as chondrichthyans, osteichthyans, and invertebrates. This coquina lag deposit records a complex taphonomic history of exhumatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although, the precise age of the LCLU and Hypolophites beckeri n. sp. requires further investigation, the regional K/Pg stratigraphy and taphonomy of LCLU chondrichthyan remains support an upper Danian–Selandian age assignment (McFarland, 2004; Becker et al, 2011, 2016; Maisch et al, in press).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Although, the precise age of the LCLU and Hypolophites beckeri n. sp. requires further investigation, the regional K/Pg stratigraphy and taphonomy of LCLU chondrichthyan remains support an upper Danian–Selandian age assignment (McFarland, 2004; Becker et al, 2011, 2016; Maisch et al, in press).…”
Section: Discussionmentioning
confidence: 93%
“…Preliminary studies on the Midway Group near Malvern, Arkansas, have identified Danian sediments in the lowermost LCLU (Dastas et al, 2010; Stringer and Sloan, 2018). However, temporal gaps are represented by the disconformity and lag deposit at the contact between the Arkadelphia Formation and Midway Group (i.e., K/Pg boundary) and the three additional lag deposits stratigraphically higher within the LCLU (e.g., Becker et al, 2010, 2013, 2016; Maisch et al, in press). Although, the precise age of the LCLU and Hypolophites beckeri n. sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations